2018
DOI: 10.1371/journal.pone.0206463
|View full text |Cite
|
Sign up to set email alerts
|

Corrected QT interval on the electrocardiogram after liver transplantation: Surrogate marker of poor clinical outcomes?

Abstract: BackgroundProlongation of corrected QT interval (QTc) on the electrocardiogram is associated with cardiac arrhythmia and sudden death. Changes in the QTc (corrected QT) interval before and after liver transplantation (LT) for the treatment of liver cirrhosis (LC) and its association with clinical outcomes have not been fully evaluated.MethodsFrom January 2011 to May 2016, consecutive 516 consecutive recipients were enrolled into LT registry and the median follow-up was 31 months (IQR 12–52). Patients with an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…( 66 ) However, posttransplant long QTc has been linked with increased risk of death. ( 67 ) As patients with pre‐existing ventricular arrhythmias are not considered for LT, there are little data regarding its impact on posttransplant outcomes. In 2020, Koshy et al developed a point‐based cardiac arrest risk index for prediction of periprocedural (30‐day) cardiac arrest and ventricular arrhythmias.…”
Section: Arrhythmiamentioning
confidence: 99%
“…( 66 ) However, posttransplant long QTc has been linked with increased risk of death. ( 67 ) As patients with pre‐existing ventricular arrhythmias are not considered for LT, there are little data regarding its impact on posttransplant outcomes. In 2020, Koshy et al developed a point‐based cardiac arrest risk index for prediction of periprocedural (30‐day) cardiac arrest and ventricular arrhythmias.…”
Section: Arrhythmiamentioning
confidence: 99%
“…Evidence suggests that it not only predicts sudden cardiac death but is also involved in its pathogenesis 18 . Studies in patients undergoing LT have evaluated the association of QT interval prolongation and cardiovascular events with mixed results 14,15,19‐21 . However, none have evaluated whether QT prolongation is associated with CA/VAs after LT 22,23 .…”
Section: Introductionmentioning
confidence: 99%
“…Similar results were presented before in smaller populations. 19 , 54 Lee et al 90 reported no significant difference in outcome when using an ECG prior to the transplant, but a 78% higher mortality if QTc prolongation was present 1 month after liver transplant.…”
Section: Risk Of Lqts In Cirrhosismentioning
confidence: 99%